FOREIGN ECONOMIC RELATIONS OF LVIV REGION OF UKRAINE - Чорний, Михайло (Human Geography Journal, 2016)
The modern state of foreign economic relations of Ukraine, Lviv region. Characterized geospatial pozpodili differences in key indicators of global economic relations on the territory of the region under study - exports and imports of goods and services, foreign direct investment, international labor migration. The map typing administrative regions in terms of participation in the global economy, based on statistical data and the use of mathematical methods kartoshemy result of this is a place of administrative districts of Lviv region in the global economic system and prepare for participation in regional economies. The priority directions of development of foreign economic relations of Lviv region.